Analysis of Business Characteristics and Motivation of Beef Cattle Farmers through an Ethnic Approach in Central Bangka Regency - Rolaz, Zavi; Andarwati, Siti; Syihabuddin, Muhammad Yasin; Hariyadi, Fransiskus Trisakti (Buletin Peternakan, 2025)
This study aims to examine the characteristics of beef cattle farming, the motivation of Malay and Chinese ethnic farmers, and to identify the factors influencing their motivation. The research was conducted from March to December 2024 in Central Bangka Regency, Bangka Belitung Islands Province, where livestock farming has become an increasingly important livelihood. A total of 100 respondents were involved, consisting of 50 Malay and 50 Chinese beef cattle farmers. Respondents were selected using purposive sampling, with the inclusion criteria being beef cattle farmers of Malay and Chinese ethnicity who resided in Pangkalan Baru District and were actively engaged in beef cattle production. Data were collected using structured questionnaires and analysed using descriptive statistics and multiple linear regression. The results show significant differences in business characteristics between the two ethnic groups, particularly in sources of finance, market access, and business orientation. Both Malay and Chinese farmers demonstrated high levels of motivation, driven by both economic and socio-cultural factors. The analysis revealed that cattle farming experience (p<0.05), cattle herd size (p<0.05), and ethnicity (p<0.01) significantly influenced farmer motivation. These findings highlight the role of ethnic background and farming experience in shaping farmers' motivation, which is essential for designing culturally sensitive livestock development strategies in the region.